A literatura indígena contemporânea no Brasil : a autoria individual e a poética do eu-nós - Peres, Julie Stefane Dorrico (2021)
This thesis proposes the concept of the poetic of I-We as a reading-key to interpret the individual authorship in the contemporary Indigenous literature. We argue that the poetic of I-We synthesizes the main characteristics of the Indigenous authorship that configurate the affirmation of writers’ ethnic belonging, such as: the signature of the traditional name and/or people’s name, the use of the mother tongue both by the presence of native words and bilingual translations, the geopolitical location, and the celebration of the nature-man paradigm. These characteristics ensembled show that individual authorship assumes the collective core of Indigenous identity, affirmed by Constitution of the Federative Republic of Brazil from 1988, by the 169 Convention of International Labor Organization in 1989, ratified by Brazil with the Decree nº 5.501, April 19th, 2004. Generally, Indigenous subjects were conceived legally as transitory categories, as beings which were in progress from primitivism to civilization, who could not live concomitantly the citizenship and the ethnic identity. In order to deconstruct the generic and racial image of the depoliticized Indian, and to reinforce his/her humanities, the Indigenous writers start to publish books in a double dynamic: the collective authorship and the individual authorship. The first is circumscribed to the context of Indigenous school education, because it is part of the differentiated public education related do Indigenous communities; the second is accessible to a broader public, inasmuch editorial distribution allows its diffusion among other cultural spaces and, consequently, a major reception – that is the reason why it has been chosen as the object of our investigation. The theoreticians who were selected to the construction of this work are Graça Graúna (2013), Daniel Munduruku (2010; 2017), Edson Kayapó (2016), Kaká Werá (2017), Ailton Krenak (2015), Jaider Esbell (2018), Márcia Wayna Kambeba (2018), and Linda Tuhiwai Smith (2018), among others.